A new approach for social vulnerability in mainland Portugal area for risk mitigation - Tavares, A. O. (2018)
The concept of Social Vulnerability (SV) is characterized by its multidimensionality. In the present study, Social Vulnerability was analyzed and evaluated according to the methodology developed by the Center for Social Studies of the University of Coimbra, which presents as innovative feature the incorporation of the Criticality and Support Capability components. Social Vulnerability was calculated for the 278 municipalities of mainland Portugal using factor analysis. The evaluation and calculation of the Criticality was carried out using 22 variables, selected from an initial number of 90, and the calculation of Support Capability was performed using 12 variables, from an initial number of 145 variables. The obtained outputs should be a working basis for the managers and stakeholders, authorities at different levels, and all the community with the objective of adopting adaptation and mitigation measures to natural and technological risks.